Cultivating Equality: Advancing Gender Research in Agriculture and Food Systems, 12-15 October 2021 - Conference Report - CGIAR GENDER Platform; Wageningen University & Research Centre (CGIAR GENDER Impact Platform, 2021)
The online conference ‘Cultivating Equality: Advancing Gender Research in Agriculture and Food Systems’ focussed on research that helps understand and advance positive synergies among sustainable and resilient agricultural, rural and food systems, and equality in societies globally.